A Review on the Progress in Chemo-Enzymatic Processes for CO2 Conversion and Upcycling - Kalaimani, Markandan; Revanthy, Sankaran; Tiong, Yong Wei; Humaira, Siddiqui *; Khalid, Mohammad; Malik, Sumira; Rustagi, Sarvesh (MDPI, 2023)
The increasing concentration of atmospheric CO2 due to human activities has resulted in serious environmental issues such as global warming and calls for efficient ways to reduce CO2 from the environment. The conversion of CO2 into value-added compounds such as methane, formic acid, and methanol has emerged as a promising strategy for CO2 utilization. Among the different techniques, the enzymatic approach based on the CO2 metabolic process in cells presents a powerful and eco-friendly method for effective CO2 conversion and upcycling. This review discusses the catalytic conversion of CO2 using single and multienzyme systems, followed by various chemo-enzymatic processes to produce bicarbonates, bulk chemicals, synthetic organic fuel and synthetic polymer. We also highlight the challenges and prospects for future progress in CO2 conversion via chemo-enzymatic processes for a sustainable solution to reduce the global carbon footprint.